Nursing care of the sick : a guide for nurses working in small rural hospitals. (New Delhi, India : AITBS Publishers, 2004)
It has been written to support nurses and nursing students working with limited resources in small rural hospitals or health centers.
Chapter 1: The role of the nurse on the health care team -- Chapter 2: Communicating with patients and their families -- Chapter 3: Monitoring the patient and recording nursing care -- Chapter 4: Daily care of teh patient -- Chapter 5: Protect the patient from infection -- Chapter 6: Safe administration of medicines -- Chapter 7: Care for the child in hospital -- Chapter 8: Care for the maternity patient -- Chapter 9: Caring for the patient who has problems with elimination -- Chapter 10: Meeting patients' nutritional needs -- Chapter 11: Care for the patient with limited mobility -- Chapter 12: Care for the surgical patient -- Chapter 13: Care for the patient in pain -- Chapter 14: Care of patients in life-threatening emergencies -- Chapter 15: Care for the dying patient and the family -- Chapter 16: preparing the patient for discharge
Includes bibliographical references.
Keywords: RURAL NURSING